2019
DOI: 10.1021/acs.jpcb.9b01159
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Raman Microscopic Detection of Follicular Thyroid Cancer Cells with Unsupervised Machine Learning

Abstract: We use Raman microscopic images with high spatial and spectral resolution to investigate differences between human follicular thyroid (Nthy-ori 3-1) and follicular thyroid carcinoma (FTC-133) cells, a well-differentiated thyroid cancer. Through comparison to classification of single-cell Raman spectra, the importance of subcellular information in the Raman images is emphasized. Subcellular information is extracted through a coarse-graining of the spectra at high spatial resolution (∼1.7 μm2), producing a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Among the possible choices for the spectral distance, we have chosen the Euclidean one, since it maximizes the similarities among the spectra. The choice to use these two methods was made to exploit their complementarity of hierarchical and non-hierarchical approaches and consequently to give solidity to the obtained results 13 , 14 , 27 29 .
Figure 6 Spread of the individual K-means clusters as a function of their number.
…”
Section: Methodsmentioning
confidence: 99%
“…Among the possible choices for the spectral distance, we have chosen the Euclidean one, since it maximizes the similarities among the spectra. The choice to use these two methods was made to exploit their complementarity of hierarchical and non-hierarchical approaches and consequently to give solidity to the obtained results 13 , 14 , 27 29 .
Figure 6 Spread of the individual K-means clusters as a function of their number.
…”
Section: Methodsmentioning
confidence: 99%
“…Deep learning (DL) uses artificial neural networks (ANNs) to circumvent this issue, and several designs such as convolutional neural networks (CNNs) in image analysis and data mining have been successfully applied to other spectroscopic techniques such as fluorescence lifetime imaging microscopy (FLIM), and multiphoton light‐sheet microscopy (Hollon et al, 2020; Krauß et al, 2018; Suzuki et al, 2019). Taylor et al (2019) reported a work on high‐resolution Raman microscopic detection of follicular thyroid cancer cells with unsupervised ML obtained a more accurate (89.8%) distinction of FTC‐133 and Nthy‐ori 3–1, in comparison to single‐cell spectra (77.6%). Moawad et al (2019) combined top‐ and sub‐level classifier identified the mallei‐complex with high sensitivities (>95%) for the identification of burkholderia mallei and related species with ML‐based Raman spectroscopic assay.…”
Section: Modality Of Raman Imaging On Tissuesmentioning
confidence: 99%
“…[ 54 ] More informative optical data can also lead to a higher accuracy in an unsupervised model. [ 55 ] Therefore, the generation and selection of high‐quality data is just as important, if not more so, than the sophisticated design of advanced ML algorithms. It is a common problem in optics community that simulated data can be generated rather easily, but experimental data is expensive.…”
Section: Brief Overviews Of Optical Data and Machine Learningmentioning
confidence: 99%
“…In this section, we will highlight some representative works. We will examine the versatility of ML algorithms in their applicability to different categories of diseases such as neoplastic, [ 26b,55,58 ] infectious, [ 25a,39,59 ] inflammatory, [ 60 ] and miscellaneous. [ 61 ]…”
Section: Cases Of Ml‐assisted Decoding Of Optical Datamentioning
confidence: 99%
See 1 more Smart Citation